Furnace for Inelastic X‐Ray Scattering from Liquids up to 1600 °C. Issue 11 (12th May 2020) - Baron, Alfred Q. R.; Inui, Masanori; Ishikawa, Daisuke; Matsuda, Kazuhiro; Kajihara, Yukio; Nakajima, Yoichi; Taguchi, Kazuhiko; Hattori, Yasunori
Abstract : The design and implementation of a furnace for inelastic X‐ray scattering from liquids with sample temperatures up to ≈1600 °C is described. Carbon composite heaters operating in vacuum provide robust heating elements: one pair of heaters has been used for >18 days of operational time above 1500 °C, including eight cycles to room temperature. High‐quality data are obtained to scattering angles as low as 7 mrad in 2 θ ( Q < 1 nm −1 at 25.7 keV) from a sample at 1560 °C. Abstract : The design and operation of a furnace for X‐ray scattering experiments from liquids is described. Carbon composite heaters operating in vacuum provide robust heating elements, with one pair of heaters used for nearly 3 weeks of operation above 1500 °C, including eight cycles to room temperature. Experiments are performed even at momentum transfers <1 nm −1 .